Composition of Delayed Age at MPV of Weight Due to Unnatural Weight Gain - Fujii, Katsunori; Tanaka, Nozomi; Hayakawa, Kentaro (British Journal of Healthcare and Medical Research, 2022)
Age at maximum peak velocity (MPV) of weight may be affected by environmental factors that cause a gap with the age at MPV of height and a delay. However, the actual situation is not clear. In this study we analyzed the shift in the age at MPV in weight caused by the difficult, stressful environment following the Great East Japan Earthquake, based on the relationship between the ages at MPV of weight and height, which is thought to be a mechanism of natural growth We also verified the mechanism of unnatural weight gain caused by the stress of the earthquake. We then determined the individual shift in the age at MPV of weight in a disaster group from a regression polynomial analysis of the age at MPV of weight against the age at MPV of height and examined the distribution state of the determined shifts. In this way, we derived evidence that the age at MPV of weight was shifted relative to the MPV age of height in girls in Fukushima Prefecture in the disaster group. This demonstrated that the effects from the Fukushima Prefecture nuclear power plant disaster were large, and also that there was a tendency for unnatural weight gain in junior high school girls in the region of Fukushima.